Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsabm.9b00488
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Doped Biphasic Calcium Phosphate: Synthesis to Application

Abstract: Among synthetic biomaterials, calcium phosphate (CaP)-based bioceramics, specifically hydroxyapatite (HA) and tricalcium phosphate (TCP) as well as biphasic calcium phosphate (BCP), are widely investigated in the biomedical community. The arrangement of different ions in the CaP crystal structure allows one to dope with metal ions, while tailoring the properties. The present article reviews some of the multifaceted research in the field of (multi)-ion-doped BCP, particularly on the aspects of biomedical applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 418 publications
3
20
0
Order By: Relevance
“…Due to this fact, many amino acids tend to adsorb on HA surface in their zwitterionic form. 48 An oft-called example is the adsorption of Gly on the HA (010) surface, as iterated in the previous section. 11 The formation of Ca-O and O-Ca-O bonds through proton transfer from amino acid to HA was evident from DFT calculation.…”
Section: Influence Of Electrostatic Interaction Energy On the Adsorptmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this fact, many amino acids tend to adsorb on HA surface in their zwitterionic form. 48 An oft-called example is the adsorption of Gly on the HA (010) surface, as iterated in the previous section. 11 The formation of Ca-O and O-Ca-O bonds through proton transfer from amino acid to HA was evident from DFT calculation.…”
Section: Influence Of Electrostatic Interaction Energy On the Adsorptmentioning
confidence: 99%
“…7 Apart from the bond formation, electrostatic interaction between the oppositely charged groups of protein and HA (COOand Ca 2+ ; NH3 + and PO4 3-) also dominates the protein adsorption, as noticed in many cases. 48,16 Another important mode of interaction is water bridge formation between protein and HA. In the case of BMP-2 adsorption on HA (001) surface, water bridged H-bonds were found to dominate the attractive interaction.…”
Section: Influence Of Electrostatic Interaction Energy On the Adsorptmentioning
confidence: 99%
“…An important number of methods were adopted by researchers to obtain BCP powders. These synthesis techniques can be generally classified into four categories, as follows: dry methods, wet chemical synthesis, high-temperature processing, and synthesis from biogenic resources (Figure 2) [101].…”
Section: From Fish Discards To Powder Preparationmentioning
confidence: 99%
“…27 The formation of strong Ca-O bonds was also noticed to mediate the interaction of HA and amino acids in its zwitterionic forms. 54 Because of this reason, zwitterionic forms of many amino acids are prone to get adsorbed on the HA surface, as many studies have reported it previously. 55,23,24 Quantum mechanical calculations reported an evidence of proton transfer from COOHgroup to HA surface during adsorption of Gly on HA (010) surface, resulting in the formation of Ca-O or O-Ca-O bond.…”
Section: Influence Of Sr 2+ Substitution On Adsorption Kineticsmentioning
confidence: 99%
“…It is now well-known that amino acids interact with the inorganic surface through electrostatic interaction and hydrogen bonds. 53,54 For HA, the electrostatic interaction occurs between the oppositely charged groups, i.e. Ca 2+ from HA and COOof amino acids and PO4 3of HA and NH3 + of the protein.…”
Section: Influence Of Sr 2+ Substitution On Adsorption Kineticsmentioning
confidence: 99%